2023
DOI: 10.1002/jpln.202300198
|View full text |Cite
|
Sign up to set email alerts
|

Faba bean (Vicia faba L.) varieties reveal substantial and contrasting organic phosphorus use efficiencies (PoUE) under symbiotic conditions

Frank K. Amoako,
Ghulam Jillani,
Saad Sulieman
et al.

Abstract: BackgroundThe excessive use of inorganic P (Pi) in soils is alarming as it is causing numerous environmental problems and may lead to the depletion of rock phosphate reserves earlier than expected. Hence, to limit the over‐dependence on Pi, there is the need to investigate organic phosphorus (Po), which is the dominant P form of soil P pool, as an alternate P source for plant growth.AimThe present study seeks to investigate organic P use efficiency of eight varieties of faba bean grown symbiotically.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…However, P supplementation did not impact NDB or SPAD (Figures 1-3). Previous evidence has suggested that plants supplied with Po can amass more or equivalent biomass to Pi [14,16,21,22]. In this present study, Po treatment obtained the highest SDB (3%), PH, and growth rate (5 and 8%) in Tiffany and Hiverna, respectively, compared with +Pi.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…However, P supplementation did not impact NDB or SPAD (Figures 1-3). Previous evidence has suggested that plants supplied with Po can amass more or equivalent biomass to Pi [14,16,21,22]. In this present study, Po treatment obtained the highest SDB (3%), PH, and growth rate (5 and 8%) in Tiffany and Hiverna, respectively, compared with +Pi.…”
Section: Discussionsupporting
confidence: 57%
“…Our group, however, was prompted by this development to research and gain insight into the effects of Po on SNF and nodulation in soil and hydroponics systems. Previously in our group, we have demonstrated that different faba bean varieties can acquire and utilize various sources of Po efficiently in soil [21,22]. These studies showed that faba bean plants supplemented with different Po sources produce equal biomass and have nodulation and SNF capacity similar to Pi.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations